Multiple Hepatic Cirrhosis Complications: Left Hepatic Hydrothorax, Upper Gastrointestinal Hemorrhage and Acute Portal Vein Thrombosis: A Case Report - Jorge Vidal Hernández Rodríguez; Adrián Rodríguez García; Olga Campesino Ramos (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2014)
Hepatic hydrothorax (HH), variceal haemorrhage (VH) and portal vein thrombosis (PVT) are complications associated with hepatic cirrhosis (HC) and involve poor prognosis.  HH occurs in 4%-17% of cirrhotic patients [1]. Atypical presentations include pleural effusion without ascites and left-sided only effusions. The pathophysiology is believed to involve defects in tendinous diaphragmatic portion. Usual treatment includes diuretics and thoracocentesis, and even transjugular intrahepatic portosystemic shunt (TIPS) and liver transplantation [2]. Among patients with cirrhosis, due to portal hypertension (PH), varices form quite frequently (10% a year, approximately), and about a third of patients with varices will develop VH. PVT is commonly developed in cirrhosis (ultrasonography studies have reported prevalence of 5 to 24 per cent), and is related to unbalanced haemostasis and slowing of portal flow.